Pathogenesis of prosthesis-related infection - Gallo, Jirí; Kolár, Milan; Novotný, Radek; Riháková, Petra; Tichá, Vlasta (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2003)
In spite of its incidence decreasing to 1% nowadays, prosthesis-related infection remains a research, diagnostic, therapeutic and cost-related problem. It can be defined as a presence of bacteria in the artificial joint space, which is significantly associated with evident laboratory and/or tissue markers, and clinical signs of running infection. We believe that the more precise understanding of pathogenesis, the more effective preventative and therapeutic measures, and the lower infection rate. The implants are colonized by airborne, skin-, and/ or surgeon-related bacteria during surgery despite being operated in closely respected operating regime. Some prosthetic characteristics are advantageous and may play important roles in the process of bacterial adherence. After successful attachment on the biomaterial surface bacteria multiply and physiologically transform into a "biofilm" community, making them much more resistant to antibiotic therapy and host immunity. Bacterial resistance is a complex phenomenon influenced by intrinsic and extrinsic factors, including the cell configuration in the biofilm community. So the cure of periprosthetic sepsis without removing of all foreign bodies and necrotic bone fragments is often ineffective. Acute hematogenous sepsis is suggestive of a distortion of a previously aseptic joint space by invasion of bacteria through the vessels.
Keywords: artroplastiky kloubů; bakteriální infekce; Arthroplasty, Replacement; biofilmy; Bacterial Infections; Joint Prosthesis; lidé; protézy kloubů; Humans; Prosthesis-Related Infections; infekce spojené s protézou; Biofilms